The tenant / Freida McFadden. - McFadden, Freida (Poisoned Pen Press, 2025)
Blake Porter is riding high, until he's not. Fired abruptly from his job as a VP of marketing and unable to make the mortgage payments on the new brownstone he shares with his fiancée, he's desperate to make ends meet. Enter Whitney. Beautiful, charming, down-to-earth, and looking for a room to rent. She's exactly what Blake's looking for. Or is she? Because something isn't quite right. The neighbours start treating Blake differently. The smell of decay permeates his home, no matter how hard he scrubs. Strange noises jar him awake in the middle of the night. And soon Blake fears someone knows his darkest secrets. Danger lives right at home, and by the time Blake realizes it, it'll be far too late. The trap is already set.